2020
DOI: 10.1088/1361-6528/abb0b6
|View full text |Cite
|
Sign up to set email alerts
|

High-performance x-ray source based on graphene oxide-coated Cu2S nanowires grown on copper film

Abstract: Full static x-ray computed tomography (CT) technology has enabled higher precision and resolution imaging and has been applied in many applications such as diagnostic medical imaging, industrial inspection and security screening. In this technique, the x-ray source section is mainly composed of a thermionic cathode and electron beam scanning system. However, they have several shortcomings such as limited scanning angle, long response time and large volume. Distributed and programmable cold cathode (i.e. carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…CoNi alloy nanoparticles and CNTs deposited N‐doped carbon nanosheet arrays on carbon cloth (CoNi alloy/NCNSAs/CC) were prepared by calcining the polymetallic organic framework precursors at 800 °C Ar/H 2 annealing. In the pyrolysis process, Co 2+ and Ni 2+ ions as the metallic nodes were simultaneously reduced to form CoNi alloy nanoparticles, and evenly embedded in N‐doped carbon nanosheet arrays and the formed alloy nanoparticles were subsequently used as the catalysts for the production of CNTs (Figure 3d) [145] …”
Section: Composition Regulation Of Mofs‐derived Self‐supported Carbon‐based Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…CoNi alloy nanoparticles and CNTs deposited N‐doped carbon nanosheet arrays on carbon cloth (CoNi alloy/NCNSAs/CC) were prepared by calcining the polymetallic organic framework precursors at 800 °C Ar/H 2 annealing. In the pyrolysis process, Co 2+ and Ni 2+ ions as the metallic nodes were simultaneously reduced to form CoNi alloy nanoparticles, and evenly embedded in N‐doped carbon nanosheet arrays and the formed alloy nanoparticles were subsequently used as the catalysts for the production of CNTs (Figure 3d) [145] …”
Section: Composition Regulation Of Mofs‐derived Self‐supported Carbon‐based Compositesmentioning
confidence: 99%
“…CoNi alloy/NCNSAs/CC showed a Tafel slope of 55 mV dec −1 , which was lowest in all samples, suggesting the favorable OER kinetics. The long‐term stability of CoNi alloy/NCNSAs/CC was tested and the data indicated that no change in polarization plots was observed after 3000 potential sweep cycles, declaring CoNi alloy/NCNSAs/CC possessed excellent catalytic stability in alkaline medium [145] …”
Section: Mofs‐derived Self‐supported Carbon‐based Composites For Oermentioning
confidence: 99%
“…Due to their excellent field emission characteristics [4][5][6], one-dimensional (1D) nanomaterials such as carbon nanotubes (CNTs) and nanowires were explored as the cold cathode for X-ray source [7][8][9]. H. Sugie et al prepared the first CNT cold cathode X-ray tube and realized X-ray transmission imaging [10].…”
Section: Introductionmentioning
confidence: 99%